PENGEMBANGAN MEDIA PEMBELAJARAN INOVATIF BERBASIS GAME QUIZIZZ UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI MADRASAH TSANAWIYAH - Syifa Khoerunnisa; Yoyo Zakaria (STKIP Subang, 2025)
This study aims to develop an innovative game-based learning media, Quizizz, to improve students' understanding of Indonesian language at Islamic Junior High Schools (Madrasah Tsanawiyah), specifically the topic